Implementasi Peraturan Daerah Provinsi Riau Tentang Penanggulangan Bencana Alam di Kabupaten Kuantan Singingi - Indri Rahayu; Sujianto (Pencerah Publishing, 2021)
Kuantan Singingi Regency is an area located near the Kuantan river, where natural disasters often occur in the river flow such as floods due to overflowing of the Kuantan river. To overcome these natural disasters, it is necessary for the local government to be agile in pursuing policies on how to cope with these natural disasters. This study uses a qualitative method which is carried out by asking questions and procedures, collecting data from participants, analyzing data inductively, and interpreting the meaning of the data. This study uses a descriptive approach which carefully records all phenomena (symptoms) that are heard, seen, and read through official documents, field notes, interviews, and personal documents. Data was collected using primary and secondary data with data collection techniques using interviews, observation, and documentation. The results in this study indicate that in dealing with natural disasters, especially floods in the Kuantan Singingi area, the government has collaborated with the Riau Province BPBD but it is still not optimal because in the Kuantan Singingi Regency area there is no BPBD, making it difficult to coordinate and give orders centrally. Therefore, more concrete policies are needed regarding disaster management in Kuantan Singingi Regency.